2019
DOI: 10.5897/ajpp2019.5060
|View full text |Cite
|
Sign up to set email alerts
|

Acquaintance of Botox: A cross-sectional survey among female students in Karachi, Pakistan

Abstract: The cosmetic treatment strategies have been considerably popular over the last few decades among the population with respect to age, gender, and ethnicity. These procedures are easily accessible safer, minimally invasive, and more precise. Botox therapy is one of the most common non-surgical cosmetic treatment. Thus, the current study was accomplished to assess the knowledge of female students towards Botox therapy for beautification as well as for therapeutic purposes. The study was conducted form June 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…In a study reported by E. M. Al Hamdan et al, Botox were commonly used to treat facial wrinkles [1]. Study reported by Imam et al showed that there was high awareness of people on Botox therapy and its effectiveness in cosmetology [6]. Therefore, this study is important to understand and increase the awareness of dentists on the use and the complications of Botox in facial aesthetics.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study reported by E. M. Al Hamdan et al, Botox were commonly used to treat facial wrinkles [1]. Study reported by Imam et al showed that there was high awareness of people on Botox therapy and its effectiveness in cosmetology [6]. Therefore, this study is important to understand and increase the awareness of dentists on the use and the complications of Botox in facial aesthetics.…”
Section: Introductionmentioning
confidence: 86%
“…It was initially introduced by Alan Scott for treating crossed eyes and blepharospasm [1]. It is called a miracle poison, which is one of the most noxious natural substances to humans [6]. It was approved by the United States Food and Drug Administration in 2002 [7,8].…”
Section: Introductionmentioning
confidence: 99%